Gender and Knowledge Shape Ethical Perceptions Among Indonesian Accounting Students: Gender dan Pengetahuan Membentuk Persepsi Etis di Kalangan Mahasiswa Akuntansi Indonesia - Rokhimulloh; Dina Dwi Oktavia Rini (Academia Open, 2024)
This study explores how gender and knowledge level influence accounting students' perceptions of unethical behavior among accountants. Conducted at Muhammadiyah University of Sidoarjo, the qualitative research involved students from the 2019 to 2022 cohorts. Data was collected through interviews, observation, and documentation, using triangulation for validation. The results show that while both male and female students have similar interpretations of ethics, female students generally have a better understanding. Additionally, higher knowledge levels correlate with a broader ethical understanding, but ethical orientation is ultimately influenced by individual morals and personal interests. Highlight: Male and female students share similar ethical interpretations. Female students exhibit better understanding of ethical concepts. Knowledge level enhances understanding, but ethics depend on morals and interests. Keyword: gender, knowledge level, unethical behavior, accounting students, qualitative study